Population Dynamic of Fruit Fly Pests Bactrocera spp. in Salacca Orchard in Relation to Host Plants and Climate Factors - Putri, Yuliani Dwi; Gunadi, Rachmad; Pranowo, Deni; Affandi, Affandi; Suputa, Suputa (AGRIVITA Journal of Agricultural Science, 2024)
Fruit flies are an economic important of pest on horticultural crops. One of the commodities that are affected much due to fruit fly attack is salacca var. pondoh. The number of fruit flies attacking salacca increased from 2018 to 2021. The aims of the research was to study the population dynamics in salacca orchards in relation to climate factors and host plants. The research was conducted from July 2022 to May 2023 in salacca orchards that are members of the Salacca Farmers Association Mitra Turindo in Wonokerto, Turi, Sleman, Yogyakarta, Indonesia. The methods were counting the number of fruit flies trapped in three observation groups with different levels of sanitation and host plants around salacca orchards. Descriptive and arithmetic methods were used to determine the pattern of population oscillation among the three observation groups and differences in sanitation levels and host plants around the salacca orchards. The result showed that population fluctuations of Bactrocera spp. in salacca orchards were correlated with rainfall and relative humidity and less correlated with temperature and wind speed. Fruit fly abundance was lower in salacca orchards with better sanitation and fewer host plants around the salacca orchard.